The dynamics of management accounting in Malaysia: a research note / Suzana Sulaiman, Aliza Ramli, Falconer Mitchell - Ramli, Aliza (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2008)
Management accounting changes take in various dimensions and are not a uniform phenomenon. The changes demand management accounting tasks, skill and tools and techniques to change. A study was conducted on Malaysian registered management accountants with CIMA Malaysian division. The findings showed that Malaysian management accountants held different job titles in various functional areas within the organization. Management accountants in the future are expected to be able to relate management accounting to wider information flow within the organization. There is a shift from ‘financial accounting’ to ‘commercial orientation’. However, traditional management accountants tasks such as cost/financial control, planning/management budget and operational information interpretation remain essential. Future management accountants are expected to be more analytical and have a broad view of business.